(3MhGTj cGed GdeHQOs - (3gTGe Hf CMeO Hf gTGe GdcfGfj CHh GdhdjO, GdeYQha HGdnhnqbpTj , J (B489 (3g` s; (3eMeO Hf jRjO Hf YHO GdCcHQ GdKeGdj GdCROj, CHh GdYHGS, GdeYQha HGdeHQO,J (B286 (3g` s
(3ChdgG (B:s
(3CeG HYO MeO Gddg ceG jLH, hGdUdGI Ydi fHjg GdefJNH aEfj LeYJ aj gPG GdLRA eG CdajJg ef GdWQQ hGdMhGTj Ydi cJGH cGed, dCHj GdYHGS GdeHQO, hLYdJ YdGeI GdefShH Edjg (B((3Pdc(B) (3aj Chd cdGeg s
(3BNQgG (B:s
(3hEfeG CQGO Cf Ef ggfG dG JJYdb HEjGce Ydi MO JYdjbgG aj bhdc EjGc hCf JaYd EPG MPQJg hEfeG JJYdb HGdcdGe GdChd JYdb GdeaYhd ef CLdg, dCfg LYd GdCeQ Ydg ef GdENQGL, dG Cfg MPQ ef GdEjeGf s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B144 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B114s
Keywords: (3GdCOHs